Effects of Dietary Protein Concentration on Ammonia Volatilization, Nitrate Leaching, and Plant Nitrogen Uptake from Dairy Manure Applied to Lysimeters. Issue 1 (1st January 2014) - Lee, Chanhee; Feyereisen, Gary W.; Hristov, Alexander N.; Dell, Curtis J.; Kaye, Jason; Beegle, Douglas
Abstract : This lysimeter experiment was designed to investigate the effects of dietary crude protein (CP) concentration on nitrate‐N (NO3 –N) and ammonia (NH3 ) losses from dairy manure applied to soil and manure N used for plant growth. Lactating dairy cows were fed diets with 16.7% CP (HighCP) or 14.8% CP (LowCP) content. Feces and urine were labeled with 15 N by ruminal pulse‐doses of 15 NH4 Cl. Unlabeled and 15 N‐labeled feces and urine were used to produce manure for a study with 21 lysimeters in a greenhouse. Manure application rate was 277 kg N ha −1 . Ammonia emissions were measured at 3, 8, 23, 28, 54, and 100 h after manure application. Manure was incorporated into the soil, and a leaching event was simulated. Spring barley was planted (387 plants per m 2 ) 7 d after the leaching event and harvested at senescence. Ammonia emission rates and the contribution of urinary N to NO3 –N were on average about 100% greater for HighCP vs. LowCP manures. With both LowCP and HighCP manures, a greater proportion of urinary vs. fecal N was recovered in leachate NO3 –N. There was no difference in whole‐crop barley N yields between LowCP and HighCP manures, but barley kernel N yield tended to be greater ( p = 0.09) for lysimeters treated with HighCP manures. Using a unique labeling approach, this lysimeter experiment demonstrated that when applied at equal soil N application rates, manure from cows fed the HighCP diet resulted in markedly greater NH3 emissions and urinary N losses with leachate NO3 –N than manure from cows fed the LowCP diet.